Fenomena Pembangunan Rumah Ibadah Agama Minoritas Di Pamekasan - Mukayat Al-Amin; Khoirul Anam (Universitas Muhammadiyah Surabaya, 2019)
AbstractBeing in a state of law which has been regulated in the law, it should be obeyed in every condition because the law is created based on community agreement to achieve comprehensive justice without favoritism. In Indonesia, religious diversity becomes a dynamic including Pamekasan, the city where the majority of the population is Muslim, so that a dynamic emerged where there is a group of religious communities who are in a minority in the city that have difficulties in building their own tabernacle.In order to get a good cooperation process, a supportive situation is needed, namely a situation that allows the creation of values which all parties can accept because they feel they need it. Even so, it is very regrettable that the ideals of salvation and peace are not always a uniform reality. Otherwise, it can occur hostility and clashes between religious groups. Keywords: Phenomenon of Tabernacle Construction of Minority Religious